Advances in eggshell membrane separation and solubilization technologies - Han, Chunhao; Chen, Yifan; Shi, Lei; Chen, Hui; Li, Lanhui; Ning, Zhonghua; Zeng, Dan; Wang, Dehe (Frontiers in Veterinary Science, 2023)
Eggshell membranes contain 90% protein, 3% lipids, 2% sugars, and small amounts of minerals such as calcium and magnesium. Of the 90% of proteins present, 472 protein species have been identified. Eggshell membranes provide the initial mineralization platform for eggshell formation, and can be used for the production of adsorbents, cosmetics, and medical products due to their special physical structure and chemical composition. Because of the special physical structure of the eggshell membrane, the disulfide bonds between and within protein molecules, and the cross-linking of lysine-derived chain and iso-chain between eggshell fibers, the eggshell membrane is difficult to dissolve, with a maximum dissolution rate of only 62%. Additionally, the insolubility of the eggshell membrane has restricted its development and utilization and consequently, any related research. Based on the physical structure and chemical composition of the eggshell membrane, this paper reviews the latest research on eggshell membrane separation and membrane protein solubilization to provide a reference for promoting the separation, dissolution, and rational development and utilization of the avian eggshell membrane.